The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5897/ajmr2014.6704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of some botanicals and bioagents against stalk and ear rot pathogen of maize, Fusarium verticillioides

Abstract: The efficacy of some botanicals and bio-agents were assessed in vitro as the potential biofungicides against Fusarium verticillioides, the causal organism of stalk rot disease of maize plant. The botanicals used in this study were Morinda lucida (Oruwo) and Tithonia diversifolia (Mexican Sunflower) and the bio-agents used were Trichoderma viride, Trichoderma harzianum, Trichoderma pseudokoningii and Bacillius subtilis. All the plant extracts and antagonistic organisms significantly inhibited the growth of Fusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In this study, we examined the potential of Jacaranda mimosifolia leaf extracts as seed treatments to protect maize against F. verticillioides. Akinbode et al 46 had demonstrated the in vitro inhibitory effects of leaf extracts of Tithonia diversifolia (Mexican sunflower) against the mycelial growth of F. verticillioides. In our study, seed treatment with J. mimosifolia extracts was found to be an effective way to control stalk rot disease while reducing the required dose of synthetic fungicide.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the potential of Jacaranda mimosifolia leaf extracts as seed treatments to protect maize against F. verticillioides. Akinbode et al 46 had demonstrated the in vitro inhibitory effects of leaf extracts of Tithonia diversifolia (Mexican sunflower) against the mycelial growth of F. verticillioides. In our study, seed treatment with J. mimosifolia extracts was found to be an effective way to control stalk rot disease while reducing the required dose of synthetic fungicide.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, effects on I. fumosorosea depended on the concentration used, either stimulating or reducing conidiogenesis. Fungal stimulation by growth-promoting substances present in plants extract has been reported (Akinbode & Ikotun 2008;Ribeiro et al 2012). In our study, independent of the fungal species, the conidia produced in culture medium under different bioinsecticide concentrations exhibited high viability (> 95%).…”
Section: Discussionmentioning
confidence: 99%
“…Stalk rot of maize is the most destructive disease worldwide and reduced yield by 10.0% (Li et al, 2010) and may increase to 30.0 to 50.0% in serious cases (Yu et al, 2017) caused by F. verticilliodes. The pathogen has been documented to be a major cause of stalk rot of maize (Akinbode et al, 2014;Christensen and Wilcoxson, 1996;Drepper and Renfro, 1990). F. verticillioides infect maize across the world, posing one of the greatest threats of toxin contamination especially fumonisin.…”
Section: Introductionmentioning
confidence: 99%
“…The stalk rot caused on maize results in stalk breakage and lodging thereby making harvesting difficult and consequently reduces yield. The fungus F. verticillioides, penetrate stalk and root directly or spread systemically in the plant after infection that originated from seed borne inoculum (Akinbode et al, 2014;Olawuyi et al, 2011;Munkvold and Desjardins, 1997).…”
Section: Introductionmentioning
confidence: 99%